Unveiling the impact of ultramicropores in carbonaceous electrode materials to boost surface-driven capacitive potassium ion storage in hybrid supercapacitors - Lee, Jiyun; Park, Jongyoon; Lim, Eunho; Hwang, Jongkook (Applied Surface Science, 2024)
Porous structure engineering has proven highly effective in enhancing the electrochemical performance of hard carbon anode materials in potassium ion hybrid supercapacitors (PIHCs). However, the relationship between the porous structure and the K+ storage behavior in these materials remains unclear, and requires further investigation. In this study, we prepare three types of carbon materials, namely micropore-dominated, ultramicropore/mesopore-mixed, and mesopore-dominated carbons, using ZnCl2 as salt template. We explore the impact of the (ultra)micropores and mesopores on the storage behavior of K+ ions in hard carbon anodes, and find that the ultramicropore volume plays a major role in enhancing the capacitive charge storage. A positive linear correlation between ultramicropore volume and capacitive K+ storage is identified for the first time. In addition, the mesopores enhance the K+ storage capacity by facilitating the transport of K+ ions and shortening their diffusion path. As a result, ultramicropore-enriched mesoporous carbon shows promise as anode material for PIHCs, achieving an energy density of 128 Wh kg−1, a power density of 9,536 W kg−1, and an outstanding capacity retention of 83.2% after 10,000 cycles at 1.0 A g−1. This study advances the fundamental understanding of porous structure design to enhance capacitive K+ storage in hard carbon materials.
Keywords: Capacitive-controled process; Controlled process; Hybrid supercapacitors; Mesopore; Porous structure design; Porous structures; Potassium ion hybrid supercapacitor; Potassium ions; Salt template; Structure design; Ultramicropores; Capacitive-controlled process; Mesopores; Porous structure design; Potassium ion hybrid supercapacitors; Salt template; Ultramicropores